Skilur almenningur íslenskt lagamál? - Ari Páll Kristinsson; Birgitta Guðmundsdóttir; Olga M. Cilia; Sigrún Steingrímsdóttir (Orð og Tunga, 2022)
Text comprehension of Icelandic legislative texts was studied qualitatively by interviewing 46 Icelandic speakers individually. The participants read parts of the Icelandic Inheritance Act no. 8/1962 and of the Icelandic Children’s Act no. 76/2003, and subsequently answered questions concerning, on the one hand, the subject matter of the texts and, on the other hand, the participants’ opinions and experience. Although the participants by and large understood the main content of the legal paragraphs, the study revealed that some of the texts could have been made easier for them to read and understand, using shorter sentences, reducing the number of inserted passages, explaining some important concepts, and by choosing more common words. Negative attitude towards legal texts in general surfaced in some interviews, and often the participants seemed to lack self-confidence and certainty about their legal rights and obligations based on what they had read in black and white.